Implications of stimulus-induced, rhythmic, periodic, or ictal discharges (SIRPIDs) in hospitalized patients - Martinez, Paola; Sheikh, Irfan; Westover, M. Brandon; Zafar, Sahar F. (Frontiers in Neurology, 2023)
Background: Stimulus induced electroencephalographic (EEG) patterns are commonly seen in acutely ill patients undergoing continuous EEG monitoring. Despite ongoing investigations, the pathophysiology, therapeutic and prognostic significance of stimulus-induced rhythmic, periodic or ictal discharges (SIRPIDs) and how it applies to specific pathologies remains unclear. We aimed to investigate the clinical implications of SIRPIDs in hospitalized patients. Methods: This is a retrospective single center study of hospitalized patients from May 2016 to August 2017. We included patients above the age of 18 and who underwent >16 hours of EEG monitoring during a single admission. We excluded patients with cardiac arrest and anoxic brain injury. Demographic data was obtained as well as admission GCS, and discharge modified Rankin Score (mRS). EEGs were reviewed for background activity in addition to epileptiform, periodic and rhythmic patterns. Presence or absence of SIRPIDs was recorded. Our outcomes were discharge mRS (good outcome mRS 0-4 and poor outcome mRS 5-6). Results: A total of 351 patients were included in the final analysis. Median age was 63 years and 175 (50%) were females. SIRPIDs were identified in 82 patients (23.4%). Patients with SIRPIDs had a median initial GCS of 12 (IQR, 6-15) and a length of stay of 12 days (IQR, 6-15). They were more likely to have absent PDR, decreased reactivity, and more likely to have spontaneous periodic and rhythmic patterns and higher frequency of burst suppression. After adjusting for baseline clinical variables, underlying disease type and severity, and EEG background features, the presence of SIRPIDs was also associated with poor outcome classified as MRS 5 or 6 (OR 4.75 [2.74 - 8.24] p=<0.0001). Conclusion: In our cohort of hospitalized patients excluding anoxic brain injury, SIRPIDs were identified in 23.4%, and were seen most commonly in patients with primary systemic illness. We found SIRPIDs were independently associated with poor neurologic outcome. Larger studies are indicated to validate these findings and determine the risks vs. benefits of anti-seizure treatment.